Pendampingan Perkembangan Anak Berkebutuhan Khusus Kategori Gifted Berdasarkan Pola Asuh Otoritatif - Sriyati; Hergyana Saras Ningtyas (UKI Press, 2021)
Children with special needs have a variety of cases. This study will focus on discussing the development of children with special needs based on authoritative parenting. The goal is that parents can understand the types and factors that cause children with special needs in the gifted category, so they can pay attention to child care appropriately. This research was conducted in October 2020 - July 2021 Lopait Village RT/RW 09/01, Tuntang, Semarang Regency, Central Java. The method used is qualitative observation conducted in the form of direct structured interviews and using google form. The data obtained are then combined so that it becomes a descriptive discussion. Based on the results of this study,